Revisiting God's Authority. - Margalit, Avishai (Social Research)
The article discusses political theology with a focus on Sunni Muslims and the Salafist movement, the authority of God, and the role of miracles in supporting religious belief. Topics include the social and political views of German political theorist Carl Schmitt, fascism and the will of God, and divine revelation and authoritative command. Additional information is presented on the significance of rebellion and revolt in Abrahamic religions, the leap of faith, and acceptance of God's authority as a matter of volition.